Waqf Optimalization To Enhance Economic Of Indonesia - M Andrio Mulasaputra; Muhammad Zilal Hamzah (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2017)
Indonesia known as the Nation with the largest Muslim citizen in the World. So do the Waqf Assets. Unfortunately, with current management couldn’t optimize the Waqf Assets. Most of Waqf Assets are Mosque and Boarding School (Pesantren). If the Waqf Asset produce revenue only to finance the operation cost Mosque and Boarding School (Pesantren). Cash Waqf nowadays more useful than Waqf Asset at form Mosque, Boarding School (Pesantren) and other assets form. In this Paper will be discuss about optimalization Waqf – either Waqf Assets or cash Waqf – as the source of funding that free from interested to enhance Economics of Indonesia with 3 (three) ways: (i). Waqf for Educations; (ii). Waqf as the source of funding to finance the start-up company; and (iii) Waqf as the working capital for Strategic Company. Keywords: Waqf, Optimalization Waqf, Economics of Indonesia